Limits to grain-legume technology integration by smallholder farmers: The case of time-sensitive labor demands and food security primacy in Malawi - Anders, E.J.; Zulu, L.C.; Jambo, E.R. (Elsevier, 2020)
Over the last two decades, researchers and farmers have been actively co-developing soil-amelioration technologies in Malawian maize-based smallholder systems, specifically grain-legume technologies (GLT) for the purpose of sustainable intensification. Despite farmers' expressed interest and researchers' technological adaptations to reflect newly discovered on-farm constraints, farmers' adoption of these technologies remains limited, as does researchers' understanding of associated barriers. We investigate Malawian-smallholder farmers' incorporation of co-designed GLT into their maize-based systems after four years of intentional on-farm experimentation, focusing on understanding farmers' (n = 366) continued low levels of integration. We used mixed qualitative and quantitative methods within participatory action research to examine the potential effects of farmers' stated preferences and perceptions of GLT on their adoption choices. We found that farmers' adoption of GLT continues to remain low. Farmers preferred their traditional maize-dominated system to the majority of the studied GLT, for its perceived superiority in meeting farmers' food security and yield needs. Additionally, although GLT were less labor intensive than farmers' traditional maize systems in aggregate, farmers' croppingsystem choices prioritized food security needs and were restricted by increased labor demand during timesensitive labor tasks that have the potential to impact food security by decreasing on-farm maize production, specifically the task of planting. We identify potential entry points for future research that prioritize reducing the planting complexity of GLT in maize-dominated systems.